Socio-Economic Development Of Lubuklinggau City 2001-2016 (Contribution Of Materials To The History Subject At State Senior High School 1 Lubuklinggau) - Diki Jayan Dika; Farida Farida; Yunani Yunani (Criksetra: Jurnal Pendidikan Sejarah, 2019)
This study entitled "The Development of the Socio-Economic Development of the City of Lubuklinggau in 2001-2016 (Contribution of Material in Historical Subjects in Lubuklinggau 1 Public High School)". The problems in this study are how the social development of Lubuklinggau City in 2001-2016 and how the economic development of Lubuklinggau City in 2001-2016. The purpose of this study was to determine the social development of Lubuklinggau City in 2001-2016 and to find out the economic development of Lubuklinggau City in 2001-2016. This study uses historical methods with steps: heuristics, source criticism, interpretation, and historiography. From the results of the study it was found that Lubuklinggau City became a municipality in 2001 after previously being the administrative city of Musi Rawas Regency. In the social field, the authors studied cover the fields of education, religion, health, poverty, security, and the economy. The increase occurred in the fields of education, religion, health and security and the decline occurred in the Ministry of Education. While in the economic field, there was an increase in both gross regional income (GRDP) and per capita income in Lubuklinggau City.